MCDONALDISASI DALAM PROGRAM TELEVISI ??COURTESY OF YOUTUBE?? - Fariza Yuniar Rakhmawati (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2013)
Abstract Indonesian television making impressions programs that utilize the content of video clips from youtube with ??Courtesy of youtube?? label as a solution to online media adaptation. Production efficiency is indicated to be the reason behind the rise of television programs Courtesy of youtube. The use of video clips downloaded for free on youtube then processed and displayed on television ads generate a lot of revenue. McDonaldisasi occurs in the form of television programs ??Courtesy of youtube?? efficiency, kalkulabilitas, predictability and control. Television programs including programs Courtesy of youtube hold rating on the size of the quantity, not the quality of the impressions. Computer system to control the pattern of impressions Courtesy of youtube, replacing the role of the media coverage by working into the role of digital technology. Dependence television rating system also lies in using the tool peoplemeter. Efficiency by downloading videos from youtube site is indicated as an activity that infringes copyright. The role of media workers for the efficient removal on impressions Courtesy of youtube. Assessment also shows the rating system indicates the irrationality as being the only benchmark that is considered to represent the tastes of viewers in Indonesia. Keyword: program, television, courtesy of youtube Televisi di Indonesia membuat program tayangan yang memanfaatkan konten dari potongan-potongan video dari youtube dengan label ??Courtesy of youtube?? sebagai solusi adaptasi dengan media online. Efisiensi produksi diindikasikan menjadi alasan di balik maraknya program televisi Courtesy of youtube. Penggunaan potongan-potongan video diunduh secara gratis di youtube kemudian diolah dan ditayangkan melalui televisi menghasilkan banyak pemasukan iklan. McDonaldisasi terjadi dalam program televisi Courtesy of youtube berupa efisiensi, kalkulabilitas, prediktabilitas dan kontrol. Program televisi termasuk program Courtesy of youtube berpegang pada ukuran kuantitas rating, bukan kualitas tayangan. Sistem komputer melakukan kontrol pada pola tayangan Courtesy of youtube, menggantikan peran peliputan oleh pekerja media menjadi peran teknologi digital. Ketergantungan televisi juga terletak pada sistem rating dengan menggunakan alat peoplemeter. Efisiensi dengan mengunduh video dari situs youtube diindikasikan sebagai aktivitas yang melanggar hak cipta. Peran pekerja media demi efisiensi dihapus pada tayangan Courtesy of youtube. Penilaian tayangan dengan sistem rating juga menunjukkan irasionalitas karena menjadi satu-satunya acuan yang dianggap merepresentasikan selera penonton di Indonesia. Kata kunci: program, televisi, courtesy of youtube